Embracing the polypill as a cardiovascular therapeutic: is this the best strategy?. (22nd November 2018) - Franczyk, Beata; Gluba-Brzózka, Anna; Jurkiewicz, Łukasz; Penson, Peter; Banach, Maciej; Rysz, Jacek
ABSTRACT: Introduction : Cardiovascular disease (CVD) is an important cause of mortality and morbidity worldwide. CVD morbidity and mortality are associated with significant financial costs related to hospitalization, medication, and lost productivity. The concept of the 'polypill' for the reduction of cardiovascular risk was proposed in 2000. A polypill is a fixed combination of drugs in a single tablet or capsule. The initial polypill consisted of three different classes of antihypertensive drugs (each at half dose), in addition to aspirin, a statin, and folic acid. The challenge today is to produce polypills containing drugs with established efficacy and complementary actions. Areas covered : The authors provide their expert perspectives on the polypill and consider the randomized clinical trials that have evaluated the safety, efficacy, adherence, and cost-effectiveness of polypills. Expert opinion : The polypill makes prescribing easier by reducing the need for complex treatment algorithms and dose titration. It also appears to be cost-effective. However, there are several issues that need to be addressed before the polypill can be used routinely. A single polypill formulation may not be suitable for all patients. It may be necessary to develop several types of polypill to meet the needs of different patient groups.